Predictability in orbital reconstruction: A human cadaver study. Part II: Navigation-assisted orbital reconstruction. Issue 10 (December 2015) - Dubois, Leander; Schreurs, Ruud; Jansen, Jesper; Maal, Thomas J.J.; Essig, Harald; Gooris, Peter J.J.; Becking, Alfred G.
Abstract: Preformed orbital reconstruction plates are useful for treating orbital defects. However, intraoperative errors can lead to misplaced implants and poor outcomes. Navigation-assisted surgery may help optimize orbital reconstruction. We aimed to explore whether navigation-assisted surgery is more predictable than traditional orbital reconstruction for optimal implant placement. Pre-injury computed tomography scans were obtained for 10 cadaver heads (20 orbits). Complex orbital fractures (Class III–IV) were created in all orbits, which were reconstructed using a transconjunctival approach with and without navigation. The best possible fit of the stereolithographic file of a preformed orbital mesh plate was used as the optimal position for reconstruction. The accuracy of the implant positions was evaluated using iPlan software. The consistency of orbital reconstruction was lower in the traditional reconstructions than in the navigation group in the parameters of translation and rotation. Implant position also differed significantly in the parameters of translation ( p  = 0.002) and rotation (pitch: p  = 0.77; yaw: p  < 0.001; roll: p  = 0.001). Compared with traditional orbital reconstruction, navigation-assisted reconstruction provides more predictable anatomical reconstruction of complex orbital defects and significantly improves orbital implant position.